PENINGKATAN HASIL BELAJAR PKn MELALUI PENERAPAN CTL - Wiwik Sudarwati (LPPM UNISDA, 2018)
This study aims to determine the improvement of PKN learning outcomes by applying Contextual Teaching and Learning (CTL) to the concept of environmental pollution. This research was carried out in SMP Negeri 2 Karangbinangun. The method used in this research is Classroom Action Research (PTK) method, PTK is implemented as an effort to overcome problems that arise in the classroom. This method is carried out in four stages, namely planning, action, observation, and reflection. These four stages are cycles that take place repeatedly and are carried out with the same steps and are focused on Contextual Teaching and Learning (CTL) learning. Based on the results of research that has been done shows that student learning outcomes have increased. This increase can be seen through the cycle that has been done. In the first cycle the average student learning outcomes were 69. While in the second cycle the average student learning outcomes were 76. Thus it can be concluded that the Contextual Teaching and Learning (CTL) learning model can improve PKN learning outcomes for students in class VI SD Negeri Banyuurip Karangbinangun on the matter of Indonesian Foreign Policy.